Analysis Of Current Ratio, Debt To Assets Ratio And Gross Profit Margin On Financial Distress With Moderated Share Prices In Retail Companies Listed In Securities Exchange - Sunaryo, Deni (International Journal of Educational Research & Social Sciences, 2021)
This study aims to determine how much influence Current Ratio (CR), Debt to Asset Ratio (DAR) and Gross Profit Margin (GPM) on Financial Distress and moderated by Stock Prices. The population in this study were 24 companies in the retail subsector listed on the Southeast Asian Stock Exchange for the period 2012-2019. The method used is purposive sampling so that 15 companies that present complete financial reports according to the variables studied and obtained as many as 105 company samples were subjected to data outliers because the data did not have a normal distribution, thus 81 samples were obtained. The analysis technique used is multiple regression analysis and Moderated Regression Analysis (MRA). The results showed that the Debt to Asset Ratio (DAR) partially affected Financial Distress, while Current Ratio (CR) and Gross Profit Margin (GPM) partially had no significant effect on Financial Distress and simultaneously CR, DAR, GPM had an effect on Financial Distress. The moderation test shows that the stock price in this study is proven to moderate the relationship of the independent variables (CR, DAR and GPM) to the dependent variable (Financial Distress).